التمكين الإداري للمرأة وعلاقته بالإبداع بالمؤسسات الرياضية - أرمنازى، نسرين عبدالله أحمد (جامعة الأسكندرية - كلية التربية الرياضية للبنين بأبوقير, 2018)
يهدف البحث إلى ثلاث أهداف أولا التعرف على مستوي تمكين المرأة بالمؤسسات الرياضية بمحافظة الإسكندرية، ثانيا التعرف على مستوي الإبداع الإداري للمرأة بالمؤسسات الرياضية بمحافظة الإسكندرية، ثالثا تحديد العلاقة بين تمكين المرأة والإبداع الإداري بالمؤسسات الرياضية بمحافظة الإسكندرية كما استخدمت الباحثة المنهج المسحي من المناهج الأساسية في البحوث الوصفية لمناسبته لطبيعة البحث، حيث أنه المنهج الذي يدرس الظاهرة قيد البحث ولا يقف عند جمع البيانات والحقائق بل يهتم بتصنيفها وتحليلها ومن ثم استخراج النتائج التي تحقق أهداف البحث وتم التطبيق على عينة قوامها (٧٥) مفردة تم اختيارها بالطريقة العشوائية البسيطة من أعضاء مجالس إدارات الأندية والعاملين بإدارات النشاط الرياضي والإدارات التابعة لها، مديري ومسئولي والعاملين بإدارات مديرية الشباب والرياضة (الإدارة العامة للشباب الإدارة العامة للرياضة إدارة الطلاع) محافظة الإسكندرية، كما تم اختيار عدد (١٥) مفردة لإجراء المعاملات العلمية لتقنين استمارة الاستبيان لها نفس خصائص عينة البحث الأساسية ومن خارجها لكي يتم إجراء الدراسة الاستطلاعية عند تقنين استمارة، كما قامت الباحثة بتصميم استمارة استبيان تم أعدادها عن طريق إتباع الأسلوب العلمي، ثم قامت الباحثة بوضع محورين للبحث المحور الأول: التمكين الإداري للمرأة وأنبثق منه (٥) أبعاد وهي: البعد الأول التفويض وحرية التصرف، البعد الثاني الكفاءة والفاعلية الذاتية، البعد الثالث تكوين فرق العمل البعد الرابع التدريب والتحفيز، البعد الخامس فاعلية الاتصال. المحور الثاني: الإبداع الإداري، ثم عرضها على السادة الخبراء (صدق المحكمين) وذلك لاستطلاع آرائهم حول مناسبتها لتحقيق هدف البحث ومعامل الاتساق الداخلي ومعامل ألفا لكرونباك لصدق وثبات عبارات ومحاور الاستبيان وجاءت أهم النتائج التفويض وحرية التصرف: وجود فرق دال إحصائيا عن عند مستوى دلالة (0.01) يرجع إلى المؤسسات الرياضية لصالح مديرية الشباب والرياضة، والجنس لصالح الذكور ويوجد تفاعل دال إحصائيا بين المؤسسات الرياضية والجنس. البعد الثاني: الكفاءة والفاعلية الذاتية: وجود فرق دال إحصائيا عن عند مستوى دلالة (0.01) يرجع إلى المؤسسات الرياضية لصالح مديرية الشباب والرياضة، ويوجد تفاعل دال إحصائيا بين المؤسسات الرياضية والجنس. البعد الثالث: تكوين فرق العمل وجود فرق دال إحصائيا عن عند مستوى دلالة (٠١. ٠) يرجع إلى المؤسسات الرياضية لصالح مديرية الشباب والرياضة، ويوجد تفاعل دال إحصائيا بين المؤسسات الرياضية والجنس، وجود فروق دالة إحصائيا في الإبداع ترجع إلى المؤسسة الرياضية والجنس، وجود فرق دال إحصائيا للإبداع الإداري لدي المرأة يرجع إلى اختلاف المؤسسة الرياضية والنوع، والمتوسطات الحسابية والانحرافات المعيارية لأبعاد استمارة الاستبيان تبعا ل المؤسسات الرياضية والجنس. ويرجع الفرق لصالح الإناث عن الذكور بالمؤسسات الرياضية يوجد تأثير دال لأبعاد تمكين المرأة على الإبداع الإداري بالمؤسسات الرياضية، ،كما أوصي البحث دعم ممارسة التمكين الإداري للمرأة بكافة أبعاده للعمل علي رفع مستوي الأداء الوظيفي لهم بالمؤسسات الرياضية، ضرورة العمل على ترسيخ مفهوم التفويض لدي القيادات الإدارية بالمؤسسات الرياضية وتوفير بيئة عمل ملائمة لدي العاملين ضرورة العمل على مشاركة كلا الجنسين من العاملين في اتخاذ القرارات وزيادة كفاءتهم وفاعليتهم نحو الأداء الوظيفي المطلوب، يجب تدريب العاملين وتطوير أفكارهم وقدراتهم ومهارتهم الوظيفية من أجل رفع مستوي أدائهم الوظيفي.
The aim of the research is to identify the level of women's empowerment in the sports institutions in Alexandria Governorate, secondly to identify the level of administrative creativity for women in the sports institutions in Alexandria Governorate, and thirdly to determine the relationship between women's empowerment and administrative creativity in the sports institutions in Alexandria Governorate. descriptive relevance to the nature of the research, as it is the approach that examines the phenomenon in question does not stop when the facts and data collection, but cares about its classification and analysis, and then extract the results that achieve the goals of the application Seathotm The Directorate of Youth and Sports (General Directorate of Youth - General Administration of Sport - Department of Talia) Governorate of Alexandria, as well as a number of members of the boards of directors of clubs and employees in the departments of sports activity and its departments, 15) Single to conduct scientific transactions exploratory study at the legalization of form, as the researcher designed a questionnaire prepared by following the scientific method, w The researcher developed two axes to search the first erasure: Administrative empowerment of women and emerged from it (5) dimensions: the first dimension of the mandate and the freedom to act, the second dimension of efficiency and self-efficacy, the third dimension is configured to work the fourth dimension of training and motivation teams, the fifth dimension of effective communication. The second axis: Administrative innovation, then presented to the experts (sincerity of the arbitrators) in order to explore their views on their suitability to achieve the goal of research and the coefficient of internal consistency and alpha lab for the Karnack to validate the consistency of the terms and axes of the questionnaire and obtained the most important results Authorization and freedom of conduct: there is a difference D statistically at the level of significance (0.01) due to the sports institutions in favor of the Directorate of Youth and Sports, sex in favor of males and there is a statistical interaction between sports institutions and sex. Second dimension: efficiency and self-efficacy: There is a difference D statistically at the level of significance (0.01) For the youth and sports, and there is a statistical interaction between the sports institutions and sex. Third dimension: the composition of the teams difference D statistically at the level of significance (0.01) due to sports institutions in favor of the Directorate of Youth and Sports, and there is a statistical interaction between sports institutions and sex, statistically in creativity due to the sports institution and sex, there is a statistically significant difference of administrative creativity among women is due to the different sports organization and type, and arithmetic averages and standard deviations of the dimensions of the questionnaire depending on the sport and sex for institutions. The difference is in favor of females than males in sports institutions. There is a significant impact on the dimensions of women's empowerment in administrative creativity in sports institutions. The study recommended supporting the practice of women's administrative empowerment in all its dimensions to work on raising the level of their performance in sports institutions.
Keywords: التمكین الإداری -- الإبداع الإدارى -- المرأة المصرية -- المؤسسات الریاضیة -- الإسكندرية